2023
DOI: 10.1021/jacs.3c02067
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the Formation Mechanism of HONO via Ammonia-Promoted Photosensitized Conversion of Monomeric NO2 on Urban Glass Surfaces

Abstract: Understanding the formation processes of nitrous acid (HONO) is crucial due to its role as a primary source of hydroxyl radicals (OH) in the urban atmosphere and its involvement in haze events. In this study, we propose a new pathway for HONO formation via the UVA-light-promoted photosensitized conversion of nitrogen dioxide (NO 2 ) in the presence of ammonia (NH 3 ) and polycyclic aromatic hydrocarbons (PAHs, common compounds in urban grime). This new mechanism differs from the traditional mechanism, as it do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…The HONO yield (Figure c) increases from 38.6% at RH0% to 69.7% at RH40%, demonstrating that the existence of water vapor strongly promotes the conversion of NO 2 to HONO on EC. It was recently found that RH significantly increases the HONO yield during the photoreaction of NO 2 in the presence of NH 3 on the urban glass surfaces, where H 2 O is considered as the hydrogen source for the HONO formation from NO 2 . In our study, after the removal of OC from soot, no sufficient protons are available for the formation of HONO on EC.…”
Section: Resultsmentioning
confidence: 65%
“…The HONO yield (Figure c) increases from 38.6% at RH0% to 69.7% at RH40%, demonstrating that the existence of water vapor strongly promotes the conversion of NO 2 to HONO on EC. It was recently found that RH significantly increases the HONO yield during the photoreaction of NO 2 in the presence of NH 3 on the urban glass surfaces, where H 2 O is considered as the hydrogen source for the HONO formation from NO 2 . In our study, after the removal of OC from soot, no sufficient protons are available for the formation of HONO on EC.…”
Section: Resultsmentioning
confidence: 65%
“…In addition, a most recent work reported that the UV-A fraction of the sunlight excites polycyclic aromatic hydrocarbons (PAHs, common OC in soot) to the triplet state and enhances the electronic interaction between the PAHs and the NO 2 , thus promoting the HONO formation in the presence of NH 3 . It is worth noting that these proposed NO 2 reduction pathways appear to be a redox reaction between NO 2 and soot rather than a catalyzed disproportionation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies over the last decade have focused on photochemical pathways for HONO formation from urban areas, ice sheets, and plant leaves. However, recently it has been suggested that the marine boundary layer (MBL) has significant daytime HONO, with the photoreduction of nitrate as a likely source. Additionally, despite the fact that HONO photodissociates within the solar actinic spectral region, its daytime concentration, especially in the MBL, has been found to reach quasi-steady-state levels, suggesting daytime photolytic sources. ,,, Recent field studies have found that nitrate photolysis reactions are likely the main contributor of photochemical HONO formation in the marine boundary layer (MBL). , The source of nitrate in the MBL comes from the displacement of chloride with nitrate in aged sea spray aerosols due to heterogeneous chemistry with gas-phase nitrogen oxides (NO 2 , HNO 3 , and N 2 O 5 ). , …”
Section: Introductionmentioning
confidence: 99%